English Learning Innovation Using Flash Card Media to Improve Students' Understanding of Vocabulary and Pronounciation - Dewi Ratnawati, Pramesti; Yulianti, Astri; Emeliana, Desi; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
Learning a language is not only being able to communicate with the language, but alsoknowing and understanding the meaning contained in the spoken word or expression. Inlearning languages, especially English, most students have difficulty in speaking.Difficulty speaking is usually caused by difficulty expressing ideas verbally, limitedvocabulary, limited grammatical skills so that it is difficult to speak with the correct rules,limited ability to pronounce words (pronounciation), making it difficult to pronounce thewords spoken correctly, lack of courage to speak for fear of being wrong. To facilitatespeaking skills, there are several effective ways to try, including: increase vocabulary(vocabulary), reading aloud. As an English teacher, it is very important to know thelearning strategies to make the learning environment more enjoyable. That is whyteachers who teach English need several strategies in the teaching and learning process,such as using flash card media to introduce vocabulary and pronunciation.